1997
DOI: 10.1192/pb.21.6.364
|View full text |Cite
|
Sign up to set email alerts
|

Reports prepared for Mental Health Review Tribunals and Managers' Reviews

Abstract: Little advice is offered in the literature for the novice report writer, despite the gravity of the situation, for example, a patient appealing against detention. Section 20, which renews the authority for detention after periods of 6 months or a year, is a useful reminder for clinicians, as it outlines the components that must be present in order for detention to continue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…1 These parameters make up the basis of metabolic syndrome as defined by the National Cholesterol Education Programme (NCEP). 2 Metabolic syndrome in turn predicts development of cardiovascular disease and diabetes. 3,4 It has been shown that secondgeneration antipsychotics contribute to the development of the syndrome.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…1 These parameters make up the basis of metabolic syndrome as defined by the National Cholesterol Education Programme (NCEP). 2 Metabolic syndrome in turn predicts development of cardiovascular disease and diabetes. 3,4 It has been shown that secondgeneration antipsychotics contribute to the development of the syndrome.…”
Section: Appendixmentioning
confidence: 99%
“…This was highlighted in 1997 by Davison & Perez de Albeniz, 'little advice is offered in the literature for the novice report writer, despite the gravity of the situation'. 2 They compiled a list of 'features to be included' in reports for mental health review tribunals and managers' reviews. Audit of reports before and after distribution of their list revealed an improvement in the quality of reports.…”
mentioning
confidence: 99%
“…Studies of the analysis of medical reports presented to tribunal hearings [63,64] are particularly instructive. A narrative of ‘endorsement’ or ratification of reports and opinions of treating personnel tended to dominate in tribunal deliberations [61].…”
Section: The Legal Approach To the ‘Challenge’ Of Psychiatric Terminomentioning
confidence: 99%
“…Studies of the analysis of medical reports presented to tribunal hearings [63,64] are particularly instructive.…”
Section: The 'Practice' Of Mental Health Lawmentioning
confidence: 99%
“…Studies of the analysis of medical reports presented to tribunal hearings [63], [64] are particularly instructive. A narrative of ‘endorsement’ or ratification of reports and opinions of treating personnel tended to dominate in tribunal deliberations [61].…”
Section: The Legal Approach To the ‘Challenge’ Of Psychiatric Terminomentioning
confidence: 99%